Low complexity video coding and the emerging HEVC standard - Ugur, Kemal; Zhang, Cixun; Norkin, Andrey; Priddle, Clinton; Rusert, Thomas; Samuelsson, Jonatan; Sjoberg, Rickard; Wu, Zhuangfei; Andersson, Kenneth; Fuldseth, Arild; Bjontegaard, Gisle; Endresen, Lars Petter; et al. (2010 Picture Coding Symposium, 2010)
This paper describes a low complexity video codec with high coding efficiency. It was proposed to the High Efficiency Video Coding (HEVC) standardization effort of MPEG and VCEG, and has been partially adopted into the initial HEVC Test Model under Consideration design. The proposal utilizes a quad-tree structure with a support of large macroblocks of size 64×64 and 32×32, in addition to macroblocks of size 16×16. The entropy coding is done using a low complexity variable length coding based scheme with improved context adaptation over the H.264/AVC design. In addition, the proposal includes improved interpolation and deblocking filters, giving better coding efficiency while having low complexity. Finally, an improved intra coding method is presented. The subjective quality of the proposal is evaluated extensively and the results show that the proposed method achieves similar visual quality as H.264/AVC High Profile anchors with around 50% and 35% bit rate reduction for low delay and random-access experiments respectively at high definition sequences. This is achieved with less complexity than H.264/AVC Baseline Profile, making the proposal especially suitable for resource constrained environments.